Security Engineering and Intelligence Informatics CD-ARES 2013 Workshops: MoCrySEn and SeCIHD, Regensburg, Germany, September 2-6, 2013. Proceedings - Cuzzocrea, Alfredo; Kittl, Christian; Simos, Dimitris E.; Weippl, Edgar; Xu, Lida.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume constitutes the refereed proceedings of two workshops: the Second International Workshop on Modern Cryptography and Security Engineering (MoCrySEn 2013) and the Third International Workshop on Security and Cognitive Informatics for Homeland Defense (SeCIHD 2013) held within the framework of the IFIP 8.4, 8.9, TC 5 International Cross-Domain Conference, CD-ARES 2013, in Regensburg, Germany, in September 2013. The 16 revised papers presented at MoCrySEn 2013 were carefully reviewed and selected from 30 submissions. They deal with symmetric-key cryptography, public-key cryptography, algorithmic cryptanalysis, software and hardware implementation of cryptographic algorithms, database encryption, and interaction between cryptographic theory and implementation issues. The 15 papers presented at SeCIHD 2013 are organized in topical sections on cyber security and dependability, network security and privacy, and multimedia technology for homeland defense.
Symmetric-key cryptography -- Public-key cryptography -- Algorithmic cryptanalysis -- Software and hardware implementation of cryptographic algorithms -- Database encryption -- Interaction between cryptographic theory and implementation issues -- Cyber security and dependability -- Network security and privacy -- Multimedia technology for homeland defense.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Data Encryption